Understanding and Practicing of Islamic Teachings among Siamese New Muslim in Kelantan, Malaysia - Don, Abd Ghafar Hj; Puteh, Anuar (SOSIOHUMANIKA, 2011)
ABSTRACT: Malaysia comprises various ethnics and races like Malays, Chinese, Indian, and also the other ethnics, including Siamese. On the Siamese, they are originally from Thailand and migrated to Kelantan, Malaysia, due to certain causes such as looking for job, acquiring knowledge, and also due to marriage bond. It is believed that the Siam community lives in Kelantan, Malaysia, possibly due to geographical factor where Kelantan State is border to Thailand. Most of Siamese are Buddhist. But nowadays, their numbers who are converted to Islam are increasing. The aim of this study is to see the degree of understanding of the New Siamese Muslim concerning Islam and their practice of Islam after their conversion. The study will focus on Siamese New Muslims in Kelantan, Malaysia. A set of questionnaire was distributed in conducting the research as to know the degree of individual knowledge of Islam and also to get the necessary information related to the subject. Library research is also used in order to support the research. The study found that all respondents have understood Islam very well and have implemented obligatory duties (worship) as a Muslim; or in another words, Islam has been a part of their life.Key words: Understanding, practicing, Islamic teachings, Siamese New Muslim, and obligatory duties in Islam.===About the Authors: Associate Prof. Dr. Abd Ghafar Hj Don and Anuar Puteh are the Lecturers at the Department of Daâwah & Leadership Studies, Faculty of Islamic Studies UKM (National University of Malaysia), 43600 UKM Bangi, Selangor Darul Ehsan, Malaysia. They can be reached at: a.g.don@ukm.my and anteh@ukm.myHow to cite this article? Don, Abd Ghafar Hj & Anuar Puteh. (2011). âUnderstanding and Practicing of Islamic Teachings among Siamese New Muslim in Kelantan, Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.1 [Mei], pp.1-12. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 2, 2011); Revised (April 6, 2011); and Published (May 20, 2011). Â  Â